Research on the influence of Siberian fir polyprenols on learning and memory of mice with an experimental model of Alzheimer's disease - Nikolay I. Suslov; Yulia S. Fedorova; Maxim L. Korobov (Research Results in Pharmacology)
Introduction: Alzheimer’s disease is increasingly becoming a cause of early disability and death. Attempts to create a pharmacotherapeutic agent that provides an effective result in treating this pathology have so far been unsuccessful. This article presents the results of experimental studies aimed at creating a more effective treatment of Alzheimer’s disease.